Concept Mapping of Career Motivation of Women With Higher Education - Kim, Min Sun (Frontiers in Psychology, 2020)
The purpose of the present study was to identify and categorize career motivations in highly educated married Korean women. Twenty five participants who are working were interviewed and asked why they continue their work despite various difficulties. Sixty-seven career persistence motivations were elicited and reliably organized into 6 categories: low interest in childcare and household labor, family-related motives, high need for achievement, financial problems/needs, self-actualization and job satisfaction, and positive perception of working women. This study is significant as it conceptualizes the motivation for career persistence as the major variable affecting highly educated married women’s decision to continue their careers and establishes the theoretical basis for future research.